Alterations of the Mice Gut Microbiome via Schistosoma japonicum Ova-Induced Granuloma - Zhao, Yanqing; Yang, Shuguo; Li, Bei; Li, Wei; Wang, Jue; Chen, Zongyun; Yang, Jing; Tan, Huabing; Li, Jian (Frontiers in Microbiology, 2019)
Schistosomiasis, also called bilharziasis, is a neglected tropical disease induced by Schistosoma spp. that causes hundreds of millions of infections. Although Schistosoma ova-induced granulomas commonly cause inflammation, hyperplasia, ulceration, micro abscess formation, and polyposis, the role of the egg granuloma on the gut microbiome remains unclear. To explore the role, gut microbial communities in mice infected with Schistosoma japonicum were surveyed. Female C57BL/6 and BALB/c mice were exposed to cercariae of S. japonicum for 45 and 65 days and then sacrificed. Intestinal contents and feces were collected, DNA was extracted, and high-throughput 16S rRNA gene-based pyrosequencing was used to provide a comparative analysis of gut microbial diversity. The intestinal mucosal tissues were also examined. Histopathologic analysis demonstrated that the basic structure of the colonic mucosa was damaged by ova-induced granuloma. Regarding the gut microbiome, 2,578,303 good-quality sequences were studied and assigned to 25,278 Operational Taxonomic Units (OTUs) at a threshold of 97% similarity. The average number of OTUs for C57BL/6 and BALB/c were 545 and 530, respectively. At the phylum level, intestinal microbial communities were dominated by Firmicutes, Bacteroidetes, Proteobacteria, and Verrucomicrobia. Infection with S. japonicum modified bacterial richness in the fecal associated microbiota. Exposure significantly modified bacterial community composition among different groups. At the phylogenetic levels, LEfSe analysis revealed that several bacterial taxa were significantly associated with the S. japonicum-infected mice. The present results suggest that egg granulomas in the intestine influence differentiation of the gut microbial community under pathophysiological conditions. This result suggests that intestinal microbiome-based strategies should be considered for early diagnosis, clinical treatment, and prognosis evaluation of schistosomiasis.